The Impact of Capital Structure and Firm Size on Financial Performance of Commercial Banks in Nepal - Chalise, Dhan Raj; Adhikari, Naba Raj (The EFFORTS, Journal of Education and Research, 2022)
This paper aimed to examine the impact of capital structure and firm size on financial performance of Nepalese commercial banks. The study used a sample of 14 commercial banks covering government owned, joint venture and private banks over the period 2013/2014– 2018/2019 with secondary sources of data. Regression analysis was used in the estimation of functions relating the Return on Assets (ROA) and Earnings per Share (EPS) with measures of capital structure and firm size (total assets). The results revealed a negative relation of ROA and EPS with capital structure (Debt/Equity). However, it showed a positive relationship of ROA and EPS with size (total assets). The findings provided the evidence in support of high-level equity capital employed in the capital structure of Nepalese commercial banks.